Pemanfaatan Pengunaan Media Audio Visual Pada Mata Pelajaran Fikih Materi Shalat Jama’ Dan Qasar - Naila Alfa Khusna (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2023)
Abstract. This research is based on the potential of teachers who teach fiqh material at MI NU Sholahiyah Kudus. The learning process here utilizes all the resources and infrastructure available at the madrasah, including projectors, speakers, computers, laptops, and so on. So that it can utilize audio-visual media in the learning process of Fiqh subjects on jama' and qasar prayers in class III at MI NU Sholahiyah Kudus. Therefore, the researcher is interested in knowing how to use audio-visual media for class III students at MI NU Sholahiyah Kudus in the subject of Jurisprudence, material for congregational prayers and qasar, he hopes students can practice it well. The method in this study is qualitative, namely by interviews, observation and documentation. The results of this study indicate that the use of audio-visual media in the Jurisprudence subject of the jama' prayer and qoshor class III at MI NU Sholahiyyah is by showing videos to students during learning so that students are able to practice how to pray jama' and qoshor properly and correctly . Keywords: Utilization, Audio Visual Media, Jurisprudence Learning